Do I stay or do I go? The Impact of Psychosocial Support Mechanisms on Student Nurses’ Decision to Complete Training - Weissenstein, Sophia (Auckland University of Technology, 2022)
New Zealand is currently facing a critical nursing shortage which is significantly affecting the quality of care that patients receive. A key contributor to this shortage is the high number of nursing students who don’t complete their studies. Therefore, increasing the number of nursing graduates joining the workforce in New Zealand is essential, as is addressing the psychosocial issues students may experience which can impede study completion. This thesis explores the psychosocial support systems offered to student nurses to understand whether their provision can help improve students’ course completion rates. The literature reviewed for this thesis identified that student nurses face many stressors and risks throughout their studies that could sabotage their training completion. This topic was investigated though a human resources management and occupational health and safety lens, which differentiates it from most of the existing literature on nursing students’ psychosocial health and relevant support mechanisms. A nationwide survey targeting students at New Zealand nursing schools was used in combination with stakeholder interviews as part of a mixed methodology. In total, 95 survey responses were gathered, and five stakeholders were interviewed. The research participants identified that the main psychosocial hazards they were exposed to while on placement were bullying, aggression, and emotional labour. Less prominent hazards included high job demands, low job control, and sexual assault. The findings of this research also suggest that poor psychosocial health (as opposed to specific interactions with the psychosocial hazards identified) is a shared factor among students considering dropping out of their studies. Further, the extent to which students understand the support systems their nursing schools offer was varied, even for students from the same institution. Of concern was that some students could not identify any psychosocial support offered, despite all schools providing some form of pastoral support and counselling. Students who were unable to access support when required, either due to barriers or a lack of knowledge, also indicated slightly higher attrition intentions when compared to students who had accessed available support systems. Therefore, student nurses must be provided with adequate support and trained in coping strategies to ensure they have the greatest chance at successfully completing their studies and being well prepared to enter the nursing workforce following graduation. To decrease attrition rates, better support is required throughout their studies, including enhanced education regarding the support already available. Nursing schools should also consider implementing additional support mechanisms for students before placement, such as education on conflict resolution techniques. Further, improved support must be offered while students are on placement, for example, by upskilling clinical educators to ensure they can provide effective support when required. By ensuring students have adequate support, they will be more likely to manage the stressors inherent in their studies, thereby giving them the best chance of success in their education and career. These measures can also contribute to alleviating the national nursing shortage by increasing the number of students entering the workforce following graduation.